1986
DOI: 10.1111/j.1469-8749.1986.tb03855.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Transverse Myelopathy in Childhood

Abstract: SUMMARY The clinical features and outcome of idiopathic acute transverse myelopathy were reviewed for 21 children aged between seven months and 14 years. Pain, most commonly in the back, was the initial symptom for 12 patients; for another six it was weakness and for two urinary retention. All patients had weakness of the legs, and 11 had arm weakness as well. Five patients had very acute onset of severe weakness and were unable to walk within three hours of onset of symptoms. Two children made no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 6 publications
6
43
0
Order By: Relevance
“…Thirty-one percent of patients recovered completely, minimal sequelae were present in 25%, and mild to severe sequelae were present in 44% (Defresne et al, 2003). A poor prognosis was associated with paraplegia and a nadir was reached within 24 hours (suggestive of vascular compromise), similar to the observations from other case series (Dunne et al, 1986;De Goede et al, 2010). This series found that use of high-dose corticosteroids was associated with a favorable outcome.…”
Section: Outcomes and Treatmentsupporting
confidence: 84%
See 4 more Smart Citations
“…Thirty-one percent of patients recovered completely, minimal sequelae were present in 25%, and mild to severe sequelae were present in 44% (Defresne et al, 2003). A poor prognosis was associated with paraplegia and a nadir was reached within 24 hours (suggestive of vascular compromise), similar to the observations from other case series (Dunne et al, 1986;De Goede et al, 2010). This series found that use of high-dose corticosteroids was associated with a favorable outcome.…”
Section: Outcomes and Treatmentsupporting
confidence: 84%
“…Two patients had recurrent ATM, and one child developed SLE, NMO, and MS. The age of onset had a bimodal distribution, with 15/47 (38%) children presenting before the age of 3 and 23/47 (49%) children presenting in adolescence, similar to prior observations from another case series (Dunne et al, 1986). At nadir, 80% of children were paraplegic and required catheterization.…”
Section: Observations From Case Seriessupporting
confidence: 83%
See 3 more Smart Citations